2005
DOI: 10.1111/j.1365-294x.2005.02578.x
|View full text |Cite
|
Sign up to set email alerts
|

Processes of diversification and dispersion of Rice yellow mottle virus inferred from large‐scale and high‐resolution phylogeographical studies

Abstract: Phylogeography of Rice yellow mottle virus (RYMV) was reconstructed from the coat protein gene sequences of a selection of 173 isolates from the 14 countries of mainland Africa where the disease occurred and from the full sequences of 16 representative isolates. Genetic variation was linked to geographical distribution and not to host species as isolates from wild rice always clustered with isolates from cultivated rice of the same region. Genetic variation was not associated to agro-ecology, viral interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 28 publications
1
38
0
1
Order By: Relevance
“…Indeed, all RYMV hosts are water-dependent species found mostly along riverbanks, lakeshores, swamps, temporary ponds and irrigation canals. For instance, wild or cultivated rice that grows along the shoreline of Lake Victoria plays the role of a corridor of susceptible hosts facilitating RYMV transmission and accounting for the close genetic relationship between isolates from Tanzania and Kenya around Lake Victoria ( Traore et al 2005). Other linear structures like rivers or roads may also facilitate the dispersal of pathogens.…”
Section: Landscape Structure and Dispersal Of Infectious Propagulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, all RYMV hosts are water-dependent species found mostly along riverbanks, lakeshores, swamps, temporary ponds and irrigation canals. For instance, wild or cultivated rice that grows along the shoreline of Lake Victoria plays the role of a corridor of susceptible hosts facilitating RYMV transmission and accounting for the close genetic relationship between isolates from Tanzania and Kenya around Lake Victoria ( Traore et al 2005). Other linear structures like rivers or roads may also facilitate the dispersal of pathogens.…”
Section: Landscape Structure and Dispersal Of Infectious Propagulesmentioning
confidence: 99%
“…In a 2-year study in Provence, Marrou et al (1979) showed that windbreaks slowed down the migration of vectors of CMV from field to field. Similarly, Traore et al (2005) analysed the spatial distribution of genetic diversity to elucidate the dispersal process of rice yellow mottle virus (RYMV), a major disease of rice in Africa. They showed a high differentiation between isolates collected in different valleys on the Tanzanian island of Pemba where rice fields are small, patchy and surrounded by forests and cultivated areas with hardly any RYMV host, habitats that act as efficient barriers to RYMV spread.…”
Section: Landscape Structure and Dispersal Of Infectious Propagulesmentioning
confidence: 99%
“…Rice yellow mottle virus 1 (RYMV1) resistance breakdown risk map: a tool to optimize the RYMV1 deployment strategy. Defined as low (right), medium (left), or high (center), the resistance breakdown risk assessed here (Table 1) and previously (Pidon et al 2017;Pinel-Galzi et al 2007Traoré et al 2010) is shown for the RYMV1 allelic series according to the geographical distribution of the strains (Pinel-Galzi et al 2015;Traoré et al 2005). The resistance breakdown risk is defined based on the representative isolates' ability to overcome the resistance of the corresponding alleles.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, strain S2-S3, which is distributed in WestAfrica, harbors the derived trait T49. This region is the geographical distribution area of O. glaberrima (Traoré et al 2005;Trovão et al 2015). Additionally, the S1 strain is divided into two main lineages, S1wa and S1ca, which correlate to their spatial distribution in West and West-Central Africa, respectively.…”
mentioning
confidence: 99%
“…However, as we were not able to detect P1 accumulation for the different mutants and WT with our polyclonal antibody (data not shown), we cannot rule out that the observed changes in RNA silencing suppression could be due to other factors, including changes in the stability of particular mutant P1 proteins. (Fargette et al, 2004;Traoré et al, 2005). The rapid evolution of the RYMV P1 could be explained by the evolutionary conflict between the RNA silencing pathway and its suppression.…”
mentioning
confidence: 99%